The Effect Of University Education On Developing Learners - Abdaoui, Fatima; Grine, Nadia (جامعة الوادي - University of Eloued, 2020)
ة لإنتاج طلبة أكفاء قادرين على حل مشاكل العمل بسهولة. في ظل هذه الإصلاحات، تتحرى هذه الدراسة تأثير البرنامج الدراسي على تنمية مهارات التفكير النقدي لدى طلبة اللغة الانجليزية كلغة أجنبية بجامعة قالمة من خلال استعمال اختبار واطسن غلازر للتفكير النقدي. تهدف الدراسة الى قياس مهارات طلبة السنة الأولى خلال الفصل الدراسي الأول وطلبة السنة الثالثة خلال الفصل الدراسي الاخير. بعد التحليل الاحصائي باستخدام اختبار العينات المستقلة، كشفت الدراسة أن الدروس المقدمة في الجامعة في اطار نظام ل.م.د. ليس لديها تأثير إيجابي على تنمية مهارات التفكير النقدي للطلبة. نتائج طلبة السنة الثالثة جاءت أدنى من نتائج طلبة السنة الأولى بالرغم من أن طلبة السنة الأولى أظهروا غياب كلي للوعي تجاه مفهوم التفكير النقدي مقارنة بطلبة السنة الثالثة الذين يمتلكون فكرة عامة عنه. بناء على النتائج المحصّلة، تمّ تقديم بعض الاقتراحات لتحسين تعليم التفكير النقدي.Abstract: The Algerian educational system has witnessed decisive reforms in the last decade to graduate competent students who can easily solve problems in workplaces, In light of these educational reforms, this paper aims at investigating the effect of the educational program on developing the critical thinking skills of learners of English as a foreign language (EFL) at the University of Guelmathrough the use of the Watson-Glaser Critical Thinking Appraisal. The study measures the skills of 28 freshmen in their first semester and 27senior EFL learners in their final semester, The age of participants ranges between 18-25 years. After a statistical analysis using an independent-sample T-test, the study reveals that the courses given at the university under the LMD reforms do not have a positive impact on developing learners’ critical thinking skills, The scores of senior learners are lower than freshmen ones though freshmen showed total lack of awareness of the concept of critical thinking in comparison to senior learners who have a general idea about it. Some recommendations to enhance teaching critical thinking are suggested based on the results reached.
مقال
Keywords: critical thinking ; university education ; EFL learners ; Watson Glaser critical thinking appraisal; التفكير النقدي؛ الدراسة الجامعية؛ طلبة اللغة االنجليزية كلغة أجنبية؛ اختبار واطسنغالزر للتفكير النقدي.